Control of Prostephanus Truncatus (Horn) (Coleoptera: Bostrichidae) Through the Treatment of Wood Used For the Construction of Maize Storage Barns - Avemegah, R.T. (University of Ghana, 1998)
The ability of the Larger Grain Borer (LGB), Prostephanus truncatus (Horn ). to bore and survive for several weeks in various wood materials led many pest control specialists to conclude that the quick and early build up of the pest in stores results from residual populations from previous infestation that survived in the wooden store structure. The relative susceptibility to P. truncatus infestation of five wood species: stems of borassus/fan palm (Borassus aethiopium (Warb.)), bam bo (Bambusa vulgaris (Schrad)), neem (Azadirachta indica (A. Juss.)) and fronds of raphia palm (Raphia hookerii (A. Chev.) and oil palm (Elaesis guineensis (A. Chev.)), which are most commonly used for store construction in the Volta Region of Ghana, was investigated. The efficacy of lindane, dursban, solignum, spent motor (engine) oil and water treatment for the protection of the above woods as store structure against LGB was also investigated. Results obtained showed marked differences among the different woods in terms of their susceptibility to LGB. Borassus stem was the most susceptible while bamboo stem and oil palm frond were the least susceptible. Lindane applied at 0.2% concentration to the surface of woods gave complete protection to all woods and killed all insects in the infested woods in laboratory trials. Dursban, though effective at 1% concentration in laboratory trials, failed to protect the same woods in a store platform in the field. Spent motor oil and solignum did not prevent infestation completely in any wood in the laboratory trial, but were effective when applied to laboratory infested woods. Results from field trials, however, indicated that only lindane solution applied as 0.4% solution to the surface of store platforms protected all the woods tested from LGB infestation. Dursban applied as 1% solution was also effective but did not protect any of the woods completely from borer infestation. Though motor oil was not effective in laboratory trials, no LGB infestation was recorded on any motor-oiltreated bamboo platform during the eight month storage period.